PENGARUH LINGKUNGAN KERJA, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KOTA SUNGAI PENUH - Efrianto Efrianto (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine: The Simultaneous Influence of Work Environment, Training, and Work Discipline on Employee Commitment The influence of work environment, training, and work discipline partially on Employee Commitment. The population of this study is all employees of the Personnel and Human Resources Development Agency of Sungai TFull City which totals 38 people. This research is to improve the conditions of the work environment, training, and work discipline according to their respective indicators and for other researchers to continue this research so that the limitations in this research can be improved